Sintered 316L/Cu/h-BN composites - E. Chusong; P. Kansuwan; R. Khosakul; N. Ohtake; P. Wila; N. Tosangthum; B. Vetayanugul; R. Tongsri (My University, 2021)
Abstract Sintered 316L/h-BN composites show high potential as self-lubricating materials, which can be applied as moving parts where lube oils and greases are not applicable and inaccessible for maintenance. The past production of such composites by sintering, faced two problems. Firstly - interaction between 316L matrix and h-BN resulting in loss of h-BN content and its lubricity. And secondly - poor 316L matrix integrity. This work employed two approaches to solve such problems. The first approach was the use of nitrogen-containing atmosphere for sintering, to retard 316L matrix and h-BN interaction. And the second approach, was copper addition to promote sintering of 316L powder particles. Sintered self-lubricating 316L/Cu/h-BN composites were produced from mixtures of 3 different 316L/Cu matrices (made by additions of 2.0, 4.0 and 6.0 wt.% copper powder to 316L powder) and 15 vol.% of h-BN powder. Green compacts of powder mixtures were sintered under cracked ammonia (75 vol.% hydrogen + 25 vol. % nitrogen) at 1300°C for 60 minutes. The sintered composites were cooled in a Linn high temperature sintering furnace. It was found that copper additions led to the decrease of densities of sintered 316L/Cu/h-BN composites, compared to that of sintered 316L/h-BN composite, due to porosity left behind by copper powder melting and dissolution. Tensile strengths of sintered 316L/Cu/h-BN composites were improved when copper contents were 4 and 6 wt.%. There was no intergranular phase, the evidence of 316L matrix and h-BN interaction in all experimental sintered composites. Microstructural observation by scanning electron microscopy (SEM) also revealed that h-BN flakes still existed in pores of sintered composites. The unreacted h-BN flakes are expected to provide lubricity of sintered composites.
Keywords: Matrix (chemical analysis); Tube furnace; Powder Metallurgy Techniques and Materials